PENYELENGGARAAN TERAS BACA SEBAGAI SOLUSI GUNA MENINGKATKAN MINAT BACA ANAK PASCA PANDEMI COVID -19 DI DUSUN 01 DESA PUNCAKSARI KECAMATAN SINDANGKERTA KABUPATEN BANDUNG BARAT - Siti Purhasanah (LPPM STAI Darul Falah, 2023)
The activity of reading books is also an activity that has many benefits and is best applied at the earliest possible age or the age of children. However, in reality very few children have very low interest in reading due to several factors. Especially like today where the development of technology is very fast and rapid, causing any information to be easily obtained through gadgets. so the activity of reading books began to be abandoned. The Teras Baca program has the aim of restoring interest in reading in children, providing reading materials for them and as a place for them to learn so that it becomes a solution for parents in motivating children to want to read. The method used in this study is a qualitative descriptive method, the data obtained from interviews and documentation are as they are, the activities are described and detailed more clearly. It is hoped that this activity can foster interest and instill reading habits for children.